Kai kurie laikų stilistinės transpozicijos atvejai lietuvių ir anglų kalbose - Steponavičiūtė, I. (Kalbotyra, 1979)
Transposition is a syntagmatic neutralization of categorial oppositions which provides the basis for the formation of contextual equivalence and adds stylistic value to a transposed form. The notional flexibility of the Lithuanian and English present tense forms accounts for their readiness to replace past and future tenses. But the reverse is less frequent. In any case tense-shift is meant to add vividness and emotional colouring to the description.